MEMBANGUN BUDAYA HUKUM INDONESIA DI ERA GLOBALISASI - Riski Febria Nurita Laga Sugiarto - (Jurnal Cahaya Keadilan, 2018)
If today we are talking about a country called the Republic of Indonesia then we will not be much to talk about corruption, bribery, conflicts both internal conflict within the three highest institution in Indonesia as well as external conflict outside the institutions of the country, fighting between students as well as fighting between citizens in Indonesia itself, persecution, murder, rape and many others that we actually own has been embarrassed to talk about it because these things will not be there eventually. Especially if we are talking about the law in the era of globalization we are not going away talking about the law in Indonesia with the name of injustice,alignments, partiality, not autonomy and others. These things when we look back carefully, we will find something called "legal culture", because the legal culture is the determinant of where the legal system is placed in its rightful place with the values ​​in it that is of social value as a law made is intended for people in a country itself to regulate all behavior of the people in the country that issued the law. Legal culture in Indonesia itself has been displaced by a culture new law caused by many things for example the rapid advancement of technology as if we can cross the boundary between countries, the development of free trade in Indonesia, information increasingly and still many other causes. The causes are the leave a good impact on our country for example, just in the field of law, with the advancement of information technology we can determine how the application of the law in the countries of the other so that we can improve a system of law in our own country if rated less well then we can take the example of the application of the law in other countries. In addition to the positive impact made by many advances in the era of globalization, the negative impact also participated and coloring everything in our country. For example, just by the appearance of a culture of western thought we became western Similarly we can see the beginning of our country is a democratic state of the people and for the people all-round social and the social interest anyway so this time indirectly our country shifted to a liberal state that is society most have a spirit of individualism, the economy shifted that originally brag about a democratic economy in this country to be an economy of capitalism has been proven in our country in power at any point economic pulse is the capital high and that no capital is still the clans marginal in their own country without any change from year to year. Shifts which is the subject of study authors that will be described one by one starting from the initial state of the legal culture in Indonesia, penetration western entering in Indonesia, state legal culture in Indonesia after the penetration of western is entered, up to How to restore the legal culture of Indonesia that has been displaced in the sense of a shift in the negative direction.